SMAD2/3-SMYD2 and developmental transcription factors cooperate with cell cycle inhibitors to guide tissue formation - Militi, S; Nibhani, R; Pook, M; Pauklin, S (Oxford University Press, 2024)
Tissue formation and organ homeostasis are achieved by precise coordination of proliferation and differentiation of stem cells and progenitors. While deregulation of these processes can result in degenerative disease or cancer, their molecular interplays remain unclear. Here we show that the switch of human pluripotent stem cell (hPSC) self-renewal to differentiation is associated with the induction of distinct cyclin-dependent kinase inhibitors (CDKIs). In hPSCs, Activin/Nodal/TGFβ signaling maintains CDKIs in a poised state via SMAD2/3-NANOG-OCT4-EZH2-SNON transcriptional complex. Upon gradual differentiation, CDKIs are induced by successive transcriptional complexes between SMAD2/3-SMYD2 and developmental regulators such as EOMES, thereby lengthening the G1 phase. This, in turn, induces SMAD2/3 transcriptional activity by blocking its linker phosphorylation. Such SMAD2/3-CDKI positive feedback loops drive the exit from pluripotency and stepwise cell-fate specification that could be harnessed for producing cells for therapeutic applications. Our study uncovers fundamental mechanisms of how cell-fate specification is interconnected to cell-cycle dynamics and provides insight into autonomous circuitries governing tissue self-formation.